"SEW" What Do We Know and Where Do We Go? A Review of Socioemotional Wealth and a Way Forward. (December 2020) - Swab, R. Gabrielle; Sherlock, Chelsea; Markin, Erik; Dibrell, Clay
This analysis provides a review of family business literature concerning the application of socioemotional wealth (SEW) and its extension through the FIBER framework. Specifically, we answer Brigham and Payne's call by assessing the multidimensionality of the SEW construct, the interrelatedness of the dimensions, and its specificity to family firms. We contribute to the literature by conducting a systematic review of the SEW literature and examining the applications of the FIBER dimensions, noting the evolution of specific research themes. Last, using necessary condition analysis, we provide four conceptual inferences regarding the assumptions of SEW to provide a way forward.